SPECIFICS OF ADOLESCENT ATTITUDE TO PHYSICAL TRAINING AND SPORTS - E.V. Antonova; N.I. Makeev; V.A. Rodionov (Union of pediatricians of Russia, 2009)
Over the past years, the role of physical education and sports in youth health improvement has deteriorated, the public status of physical training for purposes of health improvement and promotion has fallen. The article outlines the results of a study of attitudes to physical education and sports among 310 senior grades in secondary schools of the town of Zhukovsky in Moscow region under the program of research into health-saving behaviours in adolescents. Along with a low sports activity most adolescents of both sexes do not do morning exercises at all. At the same time, their overall motor performance is also at a very low level. The sedentary life style becomes a dominant feature in the development of younger generation.Key words: adolescents, attitude to sports, motor performance.